Pengaruh Beban Kerja Terhadap Kinerja Karyawan Di Hotel Four Points By Sheraton Bali Ungasan - Artawan, Putu Denny; Sukerti, Ni Nyoman; Sadjuni, Ni Luh Gde Sri (Program Studi Administrasi Perhotelan, 2023)
Employee performance is a direct description of the level of achievement and efforts of the company to realize the goals, objectives, mission and vision of the company. The success of a company is influenced by the performance of its employees, if the employee's performance is good, it will be able to improve the company's performance, while if the performance is bad, it will have an impact on decreasing the company's performance. The decline of employee performance is generally caused by several factors, one of which is due to excessive workloads that cause fatigue on the work done by employees. This study aims to determine the effect of workload on employee performance at the Four Points by Sheraton Bali Ungasan hotel. stratified random sampling technique to 49 respondents. The analysis technique used is validity test, reliability test, classical assumption test, simple linear regression analysis, coefficient of determination test and t test. The results of this research indicate that there is a significant positive effect between workload variables on employee performance at the Four Points by Sheraton Bali Ungasan Hotel. This is evidenced by the value of t count = 4.675 which is greater than the value of t table = 1.677. The results of the analysis of the coefficient of determination show the effect given is 31.7%.